MOCVD Growth of High-Quality and Density-Tunable GaAs Nanowires on ITO Catalyzed by Au Nanoparticles Deposited by Centrifugation - Wu, Dan (2015)
High-quality and density-tunable GaAs nanowires (NWs) are directly grown on indium tin oxide (ITO) using Au nanoparticles (NPs) as catalysts by metal organic chemical vapor deposition (MOCVD). Au catalysts were deposited on ITO glass substrate using a centrifugal method. Compared with the droplet-only method, high-area density Au NPs were uniformly distributed on ITO. Tunable area density was realized through variation of the centrifugation time, and the highest area densities were obtained as high as 490 and 120 NP/μm 2 for 10- and 20-nm diameters of Au NPs, respectively. Based on the vapor–liquid–solid growth mechanism, the growth rates of GaAs NWs at 430 °C were 18.2 and 21.5 nm/s for the highest area density obtained of 10- and 20-nm Au NP-catalyzed NWs. The growth rate of the GaAs NWs was reduced with the increase of the NW density due to the competition of precursor materials. High crystal quality of the NWs was also obtained with no observable planar defects. 10-nm Au NP-induced NWs exhibit wurtzite structure whereas zinc-blende is observed for 20-nm NW samples. Controllable density and high crystal quality of the GaAs NWs on ITO demonstrate their potential application in hybrid a solar cell.